Antibiotic resistance in Pseudomonas aeruginosa: mechanisms and alternative therapeutic strategies - Pang, Zheng; Raudonis, Renee; Glick, Bernard R.; Lin, Tong-Jun; Cheng, Zhenyu (Biotechnology advances, 2019)
Pseudomonas aeruginosa is an opportunistic pathogen that is a leading cause of morbidity and mortality in cystic fibrosis patients and immunocompromised individuals. Eradication of P. aeruginosa has become increasingly difficult due to its remarkable capacity to resist antibiotics. Strains of Pseudomonas aeruginosa are known to utilize their high levels of intrinsic and acquired resistance mechanisms to counter most antibiotics. In addition, adaptive antibiotic resistance of P. aeruginosa is a recently characterized mechanism, which includes biofilm-mediated resistance and formation of multidrug-tolerant persister cells, and is responsible for recalcitrance and relapse of infections. The discovery and development of alternative therapeutic strategies that present novel avenues against P. aeruginosa infections are increasingly demanded and gaining more and more attention. Although mostly at the preclinical stages, many recent studies have reported several innovative therapeutic technologies that have demonstrated pronounced effectiveness in fighting against drug-resistant P. aeruginosa strains. This review highlights the mechanisms of antibiotic resistance in P. aeruginosa and discusses the current state of some novel therapeutic approaches for treatment of P. aeruginosa infections that can be further explored in clinical practice.